An equvilent equation
remember you can do anything to an equation as long asyou do it to both sides
assuming yo have
x+y=1 and
x-3y=9
mulitply both by 2
2x+2y=2
2x-6y=18
those are equvilent
ok, solve initial
x+y=1
x-3y=9
multiply first equation by -1 and add to 2nd equation
-x-y=-1
<u>x-3y=9 +</u>
0x-4y=8
-4y=8
divide both sides by -4
y=-2
sub back
x+y=1
x-2=1
add 2
x=3
x=3
y=-2
(3,-2)
if we test it in other one
2x+2y=2
2(3)+2(-2)=2
6-4=2
2=2
yep
2x-6y=18
2(3)-6(-2)=18
6+12=18
18=18
yep
solution is (3,-2)
Step-by-step explanation:
4x²-9
4x²+6x-6x-9
4x²+6x-6x-9
2x(2x+3)-3(2x+3)
2x(2x+3)-3(2x+3)
(2-3)(2x+3)
solution
(8x-3)(2x+3)
The simplified version of this x-2z
Step-by-step explanation:
You need to start by combining like terms. You can start with the terms that have the variable x in them. By combining those terms, the equation becomes x+3y-z-3y-z.
From here, you can combine the terms 3y and -3y, which bring the equation to x-z-z.
From here, combine the terms with the variable z. This would bring the equation down too x-2z, your final answer.
Answer: 112%
Step-by-step explanation:
Let x = the cost of the shoes
If the cost of the sweater is 12% more than the cost of the shoes, then 1.12x is the cost of the sweater.
To convert the 1.12x into a percentage, multiply 1.12 by 100
This gives you: 112%